Red mud as sorbent for S02 gas cleaning - Nabilah Aminah, Lutpi (Curtin University of Technology, Sarawak Campus, 2011)
2nd CUTSE International Conference organized by Curtin Sarawak’s School of Engineering and Science in collaboration with The Institution of Engineers Malaysia (Miri Branch) was held at Curtin University of Technology Sarawak Campus, Miri Sarawak from 24th - 25th November 2009.